2017
DOI: 10.1155/2017/9823865
|View full text |Cite
|
Sign up to set email alerts
|

Response of Extreme Precipitation to Solar Activity and El Nino Events in Typical Regions of the Loess Plateau

Abstract: Extreme climatic oscillation has been the subject of global attention. The purpose of this study is to explore the response of extreme precipitation to solar activity and El Nino events in typical regions of the Loess Plateau-a case study in the Yan'an area. The precipitation data was from nine weather stations in Yan'an and the sunspot number and the Southern Oscillation Index (SOI) were from 1951 to 2015. The results show that maximum precipitation occurred mainly at the peak sunspot number or 2a near it and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Moreover, Zhang et al [50] reported that, at the peak of sunspot activity or two years near it, the summer precipitation in Xi'an, China, increased sharply. Li et al also reported that at the peak of sunspot number or two years near it, the precipitation in the Yan'an area in Chana increased [31].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, Zhang et al [50] reported that, at the peak of sunspot activity or two years near it, the summer precipitation in Xi'an, China, increased sharply. Li et al also reported that at the peak of sunspot number or two years near it, the precipitation in the Yan'an area in Chana increased [31].…”
Section: Resultsmentioning
confidence: 96%
“…More recently, Li et al studied how El Niño events and solar activity affected extreme precipitation in typical regions of the Loess Plateau in China. The authors found that at peak sunspot number events, there was the highest amount of precipitation [31]. In 2018, Dong et al used wavelet techniques to analyze the annual and decadal variations of the hydrological processes in the Yoshino River basin in Japan, to determine any interactions with either solar activity or ENSO.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The wavelet power spectrum of rainfall variability (Figure 4a) reveals significant power concentration at time scales of 8-16 years and at 11 years solar time scales [31]. A dominant amplitude mode is also seen in the low frequency range at around 1920-1940 years (at periods [30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 97%
“…The general correspondence of prominent rainfall changes with variations in solar activity implies a solar influence on area-scale rainfall oscillations during the past 116 years. So, in this paper an attempt was made to study the relationship between temperature, rainfall, and solar activity [32][33][34][35]. Figure 4(b) showed the significant peaks around the years of 1928, 1940, 1970 and 1990.…”
Section: Resultsmentioning
confidence: 99%
“…One of the controversies is the gully filling that can increase the frequency of significant disasters, such as dam breaks and landslides [31]. Several researchers have reported that about 2000 hectares of farmland were damaged by the salinization, swamping, and dam breaks after the continuous rainfall in the Yan 'an typical GLC area in 2013 [32][33][34].…”
Section: Introductionmentioning
confidence: 99%